TRI HITA KARANA BASED SUBAK IN STRENGTHENING CHARACTER AND SOCIAL STUDIES LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Kertih, I Wayan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Less than optimal learning results in the character and learning outcomes of students, where at this time the character and student learning outcomes are not optimal and can be said to be low. For this reason, research aimed at analyzing the application of Tri Hita Karana-based Subak in strengthening the character and learning outcomes of elementary school students was carried out. The research design is a quasi-experimental design in the form of a post-test group design. The research sample was 60 students consisting of 30 experimental class students and 30 control class students. Collecting research data used test and questionnaire methods. The instrument used was a test instrument in the form of a description of 10 questions to test learning outcomes, and a questionnaire instrument consisting of 30 statements, to measure learning outcomes. Data analysis methods and techniques used were quantitative descriptive analysis and inferential statistical analysis. The data analysis technique used in this research was Manova. The results indicate that there is an effect of the application of Tri Hita Karana based Subak learning on the students’ character and learning outcomes. This condition was shown from the results of data analysis where the average value of students' character and student learning outcomes who were taught with Tri Hita Karana based Subak learning was higher. In addition, the research findings also indicate that the learning outcome variable is strongly influenced by the Tri Hita Karana-based subak learning.